Life cycle assessment of an entirely wood floor system designed for carbon negativity, future adaptability, and end-of-life de/re/construction - Muzan Williams Ijeoma; Sovanroth Ou; Amin Nabati; Hao Chen; Michael Stoner; Patricia Layton; Dustin Albright; Brandon Ross; Weichiang Pang; Michael Carbajales-Dale (Environmental Research: Infrastructure and Sustainability)
The construction sector accounts for approximately 11% of global greenhouse gas emissions, largely due to the production of steel, concrete and aluminum. As global infrastructure investments grow, exceeding $2.9 trillion in the United States alone, there is an urgent need to transition to low-carbon structural systems. Mass timber offers a promising alternative, with lower embodied carbon (EC) and the potential to function as a carbon sink when sustainably sourced. However, conventional mass timber floor systems are limited to spans of 16–25 feet, depending on the selected system and thickness. They often rely on concrete toppings for acoustic and vibration performance, undermining environmental and circularity benefits. Here, we present a novel, all-wood mass timber floor system capable of spanning 40 feet, comparable to steel-framed construction, while achieving carbon negativity, modularity, and disassembly. This is the first timber-based system to combine these structural and sustainability attributes at this span-length. A cradle-to-gate life cycle assessment, aligned with EN 15978 and ISO 14044, quantified the floor system development environmental performance across two proprietary connection strategies: adhesive + screw and sharp plate + screw. Each design sequestered 4,787 kg CO _2 -eq of biogenic carbon per functional unit, contributing to a net EC of −100.6 and −96.7 kg CO _2 -eq/m ^2 , respectively, after accounting for construction-stage emissions. The Sharp Plate system also showed lower impacts in smog formation, ecotoxicity, and energy use. Our findings demonstrate the viability of long-span, low-carbon timber floor systems and highlight how connection design can meaningfully influence environmental performance in timber-floor design.